Аналого-цифровий багатофункціональний перетворювач - Мичуда, Леся; Мичуда, Зеновій (Видавництво Національного університету «Львівська політехніка», 2002)
Тhe new principle of construction of analog-to-digital multifunctional converters based on redistribution of a charge in commuted condensers is offered and the singularities of its realization are considered.